Multi drugs resistance to Diabetes Mellitus patients with tuberculosis in Manado City - Rambi, Elne Vieke; Sukandar, Dyan R; Makalew, Linda Augustien; Tomastola, Yohanis; Konoralma, Ketrina (Jurnal Teknologi Laboratorium, 2021)
Diabetes mellitus (DM) with pulmonary tuberculosis (TB) is an infectious disease if not educated regularly, there will be a high risk of drug resistance and even some anti-tuberculosis drugs. This study aims to identify anti-tuberculosis drug resistance in DM patients with TB in Manado City. The population in the study types 2 DM patients as amount 80 patients. Based on TCM/GenExpert examination from 47 respondents, there were 17 respondents positive multi drugs resistance rifampicin (RR). Sampling taking based on inclusion criteria, i.e., have had type DM for five years, had suffered TB MDR RR based on GenXpert examination as much as 17 respondents followed in the resistance test with Sputum TB culture and MGIT method. The result of the study showed that MDR DM-TB with MGIT method as followed is obtained from 17 samples, six samples (35.30%) resistance INH 0.4 mg and 1 sample (5.88%) MDR canamycin, and still sensitive INH 0.4 mg and camaycin is ten samples (58.82%). This study results could be used to program planning of prevention and controlling efforts TB-DM in this treatment obedience and regimen anti-tuberculosis medicine for MDR-TB patients.